Erik Satie's ballet "uspud": Prime Numbers and the Creation of a New Language with Only Half the Alphabet - Orledge, Robert (Musical times (London, England : 1957), 2009)
The large 'uspud' brochure of April 1893(8) shows that four of the above characters held a special fascination for Satie and were singled out as the subjects of forthcoming works in an advertisement on the final page. [...] ONTROTANCE, ballet in one act' is listed as 'in preparation' and 'CORCLERU, ballet in three acts/IRNEBIZOLLE, ballet in two acts [and]/TUMISRUDEBUDE, ballet in three acts' are listed 'for later on (God willing)'.